Dual functionality of over-lithiated NMC for high energy silicon-based lithium-ion batteries. Issue 21 (21st May 2021) - Dose, Wesley M.; Kim, Soojeong; Liu, Qian; Trask, Stephen E.; Dunlop, Alison R.; Ren, Yang; Zhang, Zhengcheng; Fister, Timothy T.; Johnson, Christopher S.
Abstract : Over lithiated Li1+ x NMCO2 is introduced as a dual-functional lithium source and cathode material to increase the lithium inventory and significantly improve the energy density and cycle life of lithium-ion batteries with a Si-based anode. Abstract : Owing to their high specific capacity and suitably low operating potential, silicon-based anodes are an attractive alternative to graphite in next-generation lithium-ion batteries. However, silicon anodes suffer from low initial coulombic efficiency and fast capacity decay, limiting their widespread application. Pre-lithiation strategies are highly appealing to compensate for irreversible active lithium loss and to boost the cell energy density. In this work, we maximize the cell energy density by direct pre-lithiation of the NMC (LiNi0.5 Mn0.3 Co0.2 O2 ) cathode to Li1+ x NMCO2 without introducing inactive deadweight to either electrode. First, we demonstrate that Li1+ x NMCO2 can be synthesized chemically, via reaction between NMC and lithium napthalide, and electrochemically. The NMC cathode is tolerant of a one-time over-lithiation up to 60 mA h gNMC −1, giving capacity retention on par with untreated NMC in half cell electrochemical cycling. Using synchrotron X-ray absorption spectroscopy ( ex situ ) and diffraction ( in situ ), we demonstrate that higher amounts of over-lithiation lead to local structure distortion – driven by transition metal reduction to Jahn–Teller active Mn 3+ and Co 2+ – as well as bulk structural hysteresis during over-lithiation and layer "buckling" that increases the amount of lithium extracted from the structure in the charged state. The Li1+ x NMCO2 with low-to-moderate over-lithiation capacity (23, 46, and 70 mA h gNMC −1 ) is proven to be a highly effective dual-purpose lithium source and cathode material in full cell tests with a commercially relevant Si–graphite anode. These cells show higher capacity, superior cycle life, and improved coulombic efficiencies when compared to those with stoichiometric NMC cathodes. This study introduces a new and simple method to pre-lithiate layered transition metal oxide cathodes, opening up new possibilities for the development of high energy density lithium-ion batteries with next-generation anodes.